Tingkat Pengetahuan PHBS Guru Wali Dan Pola PHBS Murid: (Studi di SD Inpres 60 Klamono, Kabupaten Sorong) - Riswan Riswan; Irianty Juana Anna Bertha; Fransiscus Nikodemus Hosea; Siti Farida; Erni Juwita Nelwan (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Healthy and Clean Behavior (HCB) is an endeavor to promote individual’s consciousness to improve their health. HCB components include proper hand washing, adequate fruits and vegetables intake, adequate physical activity, and clean environment maintenance. Teachers have their own portion in HCB. They can directly transfer their knowledge about HCB to their students or they can become role models to the students in their action. This study aimed to assess whether teachers’ knowledge is sufficient and how it impacts their students’ behavior. This observational study used a cross-sectional design. A total of 38 students and 3 teachers from Klamono 60 Inpres Elementary School, Sorong Regency were involved in this study. Questionnaires on HCB knowledge and HCB practice were used to evaluate both the teachers and students. All teachers (n= 3) had a good HCB knowledge while 74% of students had poor attitude towards Healthy and Clean Behavior. The knowledge of Healthy and Clean Behavior of all teachers were good while HCB practices among students were mostly poor.